"Key to Behavioral Observation of Developmental Disorders" by teachers in Greek School and the role of ICTs - Chaidi , Irene; Drigas, Athanasios (Technium Social Sciences Journal, 2022)
Children on the autism spectrum present significant difficulties in recognizing, understanding, and expressing emotions and, consequently, in their socialization. The teachers, to create a personalized education program for the students, record, through direct or systematic observation, important information regarding the manifestation of these emotions. KEY is also a recording tool OBSERVATION BEHAVIOR DEVELOPMENT DISORDERS: Key observation behavioral developmental disorders: Cohen, Stem, & Balaban (1995) (trans. D. Evangelou, ed. S. Bosniadou) in the field of emotion expression. In this paper, the observation key was administered to teachers teaching students with ASD, completed, its results are analyzed and conclusions are drawn